Digitalisasi Pembelajaran Kitab Kuning Untuk Keberlanjutan Nilai Turats - Utomo, Eko Budi; Azila, Nur; Hafid, Moh. Ali (Halaqa: Journal of Islamic Education, 2025)
The traditional way of learning kitab kuning has started to face challenges, such as limited access, reduced student interest in classical texts, and the lack of optimal use of technology in learning activities. This study aims to find a new way to keep kitab kuning learning going with the help of digital tools, without losing important values like sanad (chain of knowledge), adab (ethics), and the central role of the teacher. This research uses a descriptive qualitative approach through literature review, direct observation, and interviews with several ustadz (teachers), santri (students), and Islamic education experts. The results show that a suitable digital learning model is a mobile-based application that includes teacher voice readings, automatic translations, discussion forums, and offline accessibility. Learning methods such as sorogan and bandongan can still be applied online to preserve the pesantren atmosphere. The innovation in this study is the proposed design of digital learning that is not only modern but still rooted in pesantren traditions. In addition, the findings may support pesantren leaders and related parties in developing teacher training, learning facilities, and digital systems that fit the needs on the ground. With a careful and gradual approach, digitalizing kitab kuning can help preserve Islamic scholarly heritage while adapting to the times.